2015
DOI: 10.1002/anie.201410807
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Sustained Cycle of Hydrolysis and Etching at Solution/Solid Interfaces: A General Strategy To Prepare Metal Oxide Micro‐/Nanostructured Arrays for High‐Performance Electrodes

Abstract: Assembling micro-/nanostructured arrays on conducting substrates allows the integration of multiple functionalities into modern electronic devices. Herein, a novel self-sustained cycle of hydrolysis and etching (SCHE) is exploited to selectively synthesize an extensive series of metal oxide micro-/nanostructured arrays on a wide range of metal substrates, establishing the generality and efficacy of the strategy. To demonstrate the potential application of this method, the as-prepared NiO porous nanobelt array … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…[1] Manganese-based electrode materials,s uch as layered LiNi x Co 1ÀxÀy Mn y O 2 , [2] spinel LiNi 0.5 Mn 1.5 O 4 , [3] and layered Lirich x Li 2 MnO 3 ·(1Àx)LiNi 1/3 Mn 1/3 Co 1/3 O 2 (0 x 1) [4] have undergone af lurry of research because of their high energy and power density advantages,a swell as their low cost and high cycling performance in LIBs.Electrodes comprising 1D micro-and nanostructured materials exhibit outstanding electrochemical performances owing to the shortening of electron and lithium diffusion paths,a na ppropriate contact area between active materials and electrolyte,a nd their ability to accommodate strain (which is related to compliancyt owards structural transformation upon repeated Li + insertions and extractions). [5,6] Much effort has been expended on the synthesis of 1D microand nanostructured materials.For example,amicro-emulsion method has been reported for preparation of MnC 2 O 4 nanorods as precursors for fabrication of LiNi 0.5 Mn 1.5 O 4 porous nanorods with diameters of 100-400 nm and lengths of > 10 mm. Them aterials produced displayed discharge capacities of 140 and 109 mAh g À1 at 1C and 20 Cr ates, respectively.…”
mentioning
confidence: 99%
“…[1] Manganese-based electrode materials,s uch as layered LiNi x Co 1ÀxÀy Mn y O 2 , [2] spinel LiNi 0.5 Mn 1.5 O 4 , [3] and layered Lirich x Li 2 MnO 3 ·(1Àx)LiNi 1/3 Mn 1/3 Co 1/3 O 2 (0 x 1) [4] have undergone af lurry of research because of their high energy and power density advantages,a swell as their low cost and high cycling performance in LIBs.Electrodes comprising 1D micro-and nanostructured materials exhibit outstanding electrochemical performances owing to the shortening of electron and lithium diffusion paths,a na ppropriate contact area between active materials and electrolyte,a nd their ability to accommodate strain (which is related to compliancyt owards structural transformation upon repeated Li + insertions and extractions). [5,6] Much effort has been expended on the synthesis of 1D microand nanostructured materials.For example,amicro-emulsion method has been reported for preparation of MnC 2 O 4 nanorods as precursors for fabrication of LiNi 0.5 Mn 1.5 O 4 porous nanorods with diameters of 100-400 nm and lengths of > 10 mm. Them aterials produced displayed discharge capacities of 140 and 109 mAh g À1 at 1C and 20 Cr ates, respectively.…”
mentioning
confidence: 99%
“…It can be observed that the cycle plots can be divided into two groups, the group (I) with good cycling stability is measured in the 2Zn0Mg, 1.5Zn0.5Mg, and 1.0Zn1.0Mg electrolytes, while the other group (II) tested in the 0.5Zn1.5Mg and 0Zn2Mg electrolytes shows an obvious capacity fading. Besides, it can also be realized that the specific capacity of each system increases over several cycles until to a maximum value (the first 50 cycles for group I, and the first 10 cycles for group II), indicating that an activation is required to improve the kinetics and the discharge capacity then can be fully displayed [13,[28][29][30].…”
Section: Electrochemical Behaviors Of the Mgvo Electrodes In Five Difmentioning
confidence: 99%
“…Various micro/nanostructured NiO and MnO 2 materials have been fabricated to overcome the above drawbacks. [20][21][22][23] It is demonstrated that tubular metal oxides materials have exhibited enhanced lithium storage performance due to their advantageous features for the Li + ion insertion and the volume buffering during charge/discharge process.…”
mentioning
confidence: 99%